Issues in Central Bank Finance and Independence - Lonnberg, Ake (IMF Working Papers; Working Paper ;, 2008)
Conventional economic policy models focus only on selected elements of the central bank balance sheet, in particular monetary liabilities and sometimes foreign reserves. The canonical model of an "independent" central bank assumes that it chooses money (or an interest rate), unconstrained by a need to generate seignorage for itself or government. While a long line of literature has emphasized the dangers of fiscal dominance influencing the conduct of monetary policy the idea that an independent central bank could be constrained in achieving its policy objectives by its own balance sheet situation is a relatively novel idea considered in this paper. If one accepts this potential constraint as a valid concern, the financial strength of the central bank as a stand alone entity becomes highly relevant for ascertaining monetary policy credibility. We consider several strands of evidence that clearly indicate fiscal backing for central banks cannot be assumed and hence financial independence is relevant to operational independence. First we examine 135 central bank laws to illustrate the variety of legal approaches adopted with respect to central bank financial independence. Second, we examine the same data set with regard to central bank recapitalization provisions to show that even in cases where the treasury is nominally responsible for maintaining the central bank financially strong, it may do so in purely a cosmetic fashion. Third, we show that, in actual practice, treasuries have frequently not provided central banks with genuine financial support on a timely basis leaving them excessively reliant on seignorage to finance their operations and/or forcing them to abandon policy objectives.